2014
DOI: 10.1007/s00428-014-1589-3
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput mutation profiling improves diagnostic stratification of sporadic medullary thyroid carcinomas

Abstract: Sporadic medullary thyroid carcinoma (MTC) harbors RET gene somatic mutations in up to 50 % of cases, and RAS family gene mutations occur in about 10 %. A timely and comprehensive characterization of molecular alterations is needed to improve MTC diagnostic stratification and design-tailored therapeutic approaches. Twenty surgically resected sporadic MTCs, previously analyzed for RET mutations by Sanger sequencing using DNA from formalin-fixed paraffin-embedded samples, were investigated for intragenic mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 24 publications
4
66
1
1
Order By: Relevance
“…Overall, RAS mutations were present in 69.2% (18/26) of the RET WT cases and in only 2.5% of the RET-positive sporadic MTC (P!0.0001), suggesting that activation of the protooncogenes RAS and RET represents alternative genetic events in sporadic MTC tumorigenesis. These results were confirmed by other groups , Schulten et al 2011, Boichard et al 2012, Mian et al 2012, Tamburrino et al 2012, Ciampi et al 2013, Nikiforova et al 2013, Lyra et al 2014, Simbolo et al 2014, Pennelli et al 2015. We found no other mutations in the entire coding region of the genes HRAS, KRAS and RET in the RET and RAS WT sporadic MTC (M M Moura, B M Cavaco and V Leite, unpublished observations).…”
Section: Ras Mutations In Mtcsupporting
confidence: 91%
“…Overall, RAS mutations were present in 69.2% (18/26) of the RET WT cases and in only 2.5% of the RET-positive sporadic MTC (P!0.0001), suggesting that activation of the protooncogenes RAS and RET represents alternative genetic events in sporadic MTC tumorigenesis. These results were confirmed by other groups , Schulten et al 2011, Boichard et al 2012, Mian et al 2012, Tamburrino et al 2012, Ciampi et al 2013, Nikiforova et al 2013, Lyra et al 2014, Simbolo et al 2014, Pennelli et al 2015. We found no other mutations in the entire coding region of the genes HRAS, KRAS and RET in the RET and RAS WT sporadic MTC (M M Moura, B M Cavaco and V Leite, unpublished observations).…”
Section: Ras Mutations In Mtcsupporting
confidence: 91%
“…The prevalence of RET somatic mutations (57,8%) in our analysed group is consistent with previous reports [15,[29][30][31], where the frequency of somatic RET mutation ranges between 38% [29] and 71% [15]. Moreover, similarly to other data [29,30], the most frequent somatic RET mutation in our group was M918T, which constituted nearly 50% of all RET somatic mutations.…”
Section: Discussionsupporting
confidence: 92%
“…However, when we look at Italian results only, some differences may also be noticed. Ciampi et al reported a very low prevalence of RAS mutation in RET-negative sporadic MTC (17.6%) [32] while in the Scarpa and Fugazzola group the frequency of RAS mutation was 57% [31]. This percentage was even higher in our group -68.7 % of RET-negative tumours showed RAS mutation.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…These studies reported few additional somatic alterations and recurrent mutations only in the gene MDC1, which was not profiled in this study [32,33].…”
Section: Discussionmentioning
confidence: 58%